Chopped fiber toughened high-entropy carbide ceramic used in ultrahigh-temperature extreme environment as well as preparation method and application of chopped fiber toughened high-entropy carbide ceramic

By introducing 5%-20% chopped fibers into high-entropy carbide ceramics and using carbon thermal reduction and SPS sintering processes, the problem of insufficient toughness of high-entropy carbide ceramics is solved, and the ceramics are realized under ultra-high temperature extreme environments excellent mechanical properties.

CN119409503AActive Publication Date: 2025-02-11NORTHWESTERN POLYTECHNICAL UNIV

Patent Information

Application Number
CN202411553726.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-03
Publication Date
2025-02-11
Estimated Expiration
2044-11-03

AI Technical Summary

Technical Problem

Due to its high brittleness and low ductility, high entropy carbide ceramics limit their development in engineering applications, and existing toughening methods are difficult to achieve while improving toughness and maintaining performance.

Method used

High-entropy carbide ceramics were toughened by chopped fibers (SiC, C, W) with volume fractions of 5%-20%, and ceramics were prepared by carbothermal reduction and SPS sintering processes.

Benefits of technology

It has achieved excellent mechanical properties of high-entropy carbide ceramics, reaching a fracture toughness of about 9.9446MPa.m-1/2, and is suitable for ultra-high temperature extreme environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119409503A_ABST
    Figure CN119409503A_ABST
Patent Text Reader

Abstract

The invention relates to chopped fiber toughened high-entropy carbide ceramic used in an ultrahigh-temperature extreme environment as well as a preparation method and application thereof. The chopped fiber toughened high-entropy carbide ceramic comprises chopped fibers with the volume fraction of 5%-20%, and a matrix is high-entropy carbide. The high-entropy carbide is toughened by adopting the chopped fibers, the SiC, W and C fibers all have the advantages of good high-temperature resistance, excellent mechanical properties and the like, and the chopped fiber form can ensure that the preparation process is simple and convenient, the toughening effect is relatively good, and anisotropy of performance and the like do not exist; the chopped fiber toughened high-entropy carbide ceramic prepared by the invention can reach about 9.9446 MPa.m <-1 > / 2, and has excellent mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to carbide ceramics and preparation methods, and relates to a chopped fiber toughened high entropy carbide ceramic used in ultra-high temperature extreme environment and a preparation method and application thereof. Background Art

[0002] High entropy materials have four unique effects: high entropy effect that can improve thermal properties, lattice distortion effect that can improve mechanical properties, hysteresis diffusion effect that improves high-temperature stability, and synergistic cocktail effect that integrates the advantages of each component. They have great application prospects in extreme environments.

[0003] In recent years, researchers have introduced high entropy effect into carbides with advantages such as high hardness, high melting point and good high temperature stability, so that high entropy carbides have excellent comprehensive properties such as good high temperature mechanical properties, high hardness, good radiation resistance while avoiding irradiated amorphous, and resistance to steam oxidation. These make high entropy carbides have great development prospects in nuclear structural materials and aerospace structural materials.

[0004] However, high entropy carbide ceramics have the high brittleness and low ductility brought by the ceramic material itself, which greatly limits the engineering application of high entropy carbide ceramics. At this stage, it is urgently needed to select a suitable toughening method to improve its toughness. The strong covalent bonds and low self-diffusion of high entropy carbide ceramics themselves require extremely high temperatures for their preparation, which puts extremely high demands on toughening materials.

[0005] In recent years, the main toughening methods include long fiber toughening, layered structure toughening, particle toughening, and whisker toughening. Long fiber toughening usually has anisotropy of performance, layered structure toughening has poor shear strength, particle toughening has poor effect, and whisker toughening is too difficult to disperse. Therefore, the current toughening methods used for high entropy carbide ceramics have shortcomings. Summary of the invention

[0006] Technical issues to be solved

[0007] In order to avoid the shortcomings of the prior art and solve the problem that it is difficult to balance the comprehensive mechanical properties and toughening effects of the existing high entropy carbide ceramic toughening methods, the present invention proposes a chopped fiber toughened high entropy carbide ceramic for use in ultra-high temperature extreme environments and a preparation method and application thereof.

[0008] Technical Solution

[0009] A chopped fiber toughened high entropy carbide ceramic for use in ultra-high temperature extreme environments, characterized in that it includes chopped fibers with a volume fraction of 5%-20%, and a matrix of high entropy carbide; the high entropy carbide is a mixture of TiC, NbC, TaC, VC, Mo and C powders; the chopped fibers include SiC, C and W.

[0010] The molar ratio of TiC, NbC, TaC, VC, Mo and C is 1:1:1:1:1:1.5-2.

[0011] The particle size range of TiC, NbC, TaC, VC and Mo is 1-5 μm; the particle size range of carbon powder is 10-50 nm.

[0012] The length of the chopped fibers is 1-10 mm, the diameters of SiC and C fibers are in the range of 1-20 μm, and the diameter of W fibers is in the range of 50-150 μm.

[0013] A method for preparing the chopped fiber toughened high entropy carbide ceramic for use in ultra-high temperature extreme environments, characterized by the following steps:

[0014] Step 1: Mix TiC, NbC, TaC, VC, Mo and C powders and perform high-energy ball milling to obtain mixed powder;

[0015] Step 2, carbothermal reduction: pre-press the powder into blocks and perform carbothermal reduction reaction in a vacuum furnace without pressure to remove a small amount of oxygen in the commercial powder to obtain a preform;

[0016] The carbon thermal reduction process is: heating up to 1500-1800°C at a rate of 5-10°C / min, keeping the temperature for 2-3h; cooling down to 500°C at a rate of 5-10°C / min, and then naturally cooling to room temperature with the furnace to obtain a ceramic product after carbon thermal reduction reaction and preliminary diffusion;

[0017] Step 3: Grind the carbon thermally reduced ceramic product into powder;

[0018] Step 4, fiber deposition interface and mixing: SiC or C fiber is cut to 1-10 mm, and BN interface is deposited by CVI method for short fiber C; PyC interface is deposited by CVI method for short SiC fiber; Y2O3 is deposited by magnetron sputtering method for W fiber, and then cut to 1-10 mm length as short fiber;

[0019] Step 5, mixing fibers and matrix powder: mixing the fibers with the powder after the interface deposition, mixing the C and SiC chopped fibers by stirring, wet ball milling, and vacuum precipitation in turn; mixing the W chopped fibers in a natural state; and then mixing the two to obtain a mixed powder;

[0020] Step 6, SPS sintering: the mixed powder is placed in a graphite mold and sintered by an SPS method to obtain a chopped fiber-toughened high-entropy carbide ceramic for use in ultra-high temperature extreme environments;

[0021] The SPS sintering process parameters are as follows: heating to 1800-2100°C at 50-200°C / min, increasing the pressure to 30-40MPa, and keeping the temperature at 1800-2100°C and 30-40MPa for 10-20min; cooling to 50-200°C / min after the insulation, and cooling naturally in the furnace; and obtaining short fiber-toughened high-entropy carbide ceramics for use in ultra-high temperature extreme environments.

[0022] In the step 1, the powder is poured into an agate ball mill and tungsten carbide grinding balls are added, the ball mill speed is 300-400 r / min, and the ball milling is performed for 12-24 hours; after the ball milling is completed, the obtained powder is sieved using a sieve to obtain a matrix powder.

[0023] The mass ratio of the tungsten carbide grinding balls to the powder is 5-10:1; during the wet grinding, the mass ratio of the SiC, C chopped fibers plus the powder, the ethanol, and the grinding balls is 1:5:5-10.

[0024] In the step 3: during carbon thermal reduction, the ambient pressure is required to be 95-98 MPa lower than the external atmospheric pressure.

[0025] In the step 5: pour anhydrous ethanol into a beaker and then slowly put in the fiber, use a vertical stirrer to stir at 400 r / min for 2 hours, then pour the powder into the ethanol and fiber mixture, evacuate and wet grind at 300 r / min for 12-24 hours, after wet grinding, place in a vacuum negative pressure environment for 2 hours to allow the powder fiber mixture to precipitate, and then dry in an oven at 70°C for 6-8 hours.

[0026] An application of the short fiber toughened high entropy carbide ceramics for ultra-high temperature extreme environment, characterized in that: the short fiber toughened high entropy carbide ceramics reach 9.9446MPa.m -1 / 2 , excellent mechanical properties, used in ultra-high temperature extreme environments.

[0027] Beneficial Effects

[0028] The present invention proposes a short-fiber-toughened high-entropy carbide ceramic for use in ultra-high temperature extreme environments, as well as a preparation method and application. The short-fiber-toughened high-entropy carbide ceramic includes short-fibers with a volume fraction of 5%-20%, and the matrix is ​​a high-entropy carbide. The present invention uses short-fibers to toughen high-entropy carbides. SiC, W, and C fibers all have the advantages of good high-temperature resistance and excellent mechanical properties. The use of short-fiber forms can ensure a simple preparation process, good toughening effect, and no anisotropy of performance. The short-fiber-toughened high-entropy carbide ceramic prepared by the present invention can reach 9.9446MPa.m -1 / 2 About, excellent mechanical properties.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] (1) The present invention discloses a chopped fiber toughened high entropy carbide ceramic for use in ultra-high temperature extreme environments. The raw materials include 5%-20% by volume of chopped SiC or W or C fibers, and the rest are carbides, metals, and carbon powders. At present, the toughening methods for high entropy carbides use long fibers, layered structures, particles, and whiskers for toughening. It is difficult to achieve both toughening effect and simple preparation, which greatly limits the application of high entropy carbides. The present invention uses chopped fibers to toughen high entropy carbides. SiC, W, and C fibers all have the advantages of good high temperature resistance and excellent mechanical properties. The use of chopped fibers can ensure a simple preparation process, good toughening effect, and no anisotropy in performance. The chopped fiber toughened high entropy carbide ceramic prepared by the present invention can reach 9.9446MPa.m -1 / 2 About, excellent mechanical properties.

[0031] (2) The present invention provides a method for preparing chopped fiber-toughened high-entropy carbide ceramics, which comprises heat-treating the raw material powder by a carbon thermal reduction method, mixing the powder with the chopped fibers, and finally preparing the ceramics by an SPS sintering process. At present, the oxygen content in commercial carbide powder is relatively high. Direct mixing can easily lead to oxidation of the chopped fibers at high temperatures, causing the chopped fibers to lose their toughening effect. It can also cause uneven elements or even a second phase in the matrix, resulting in poor matrix performance, thereby reducing the performance of the chopped fiber-toughened high-entropy carbide ceramics. The present invention adds excess C powder and uses a carbon thermal reduction process to perform a pressureless heat treatment on the powder, so that C and O react to generate gas to escape, which greatly reduces the oxygen content in the powder, thereby making the element distribution uniform and without segregation, reducing the content of low-density oxides, and improving the density, thereby ensuring the density and uniformity of the matrix. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a SEM image of the C chopped fiber toughened high entropy carbide ceramic prepared in Example 1 of the present invention.

[0033] Figure 2 This is a picture of the fracture morphology of the C chopped fiber toughened high entropy carbide ceramic prepared in Example 1 of the present invention after the fracture toughness test.

[0034] Figure 3 These are the fracture toughness test results of the chopped fiber toughened high entropy carbide ceramics and pure ceramic (TiTaNbVMo)C prepared in Examples 1, 2 and 3 of the present invention.

[0035] Figure 4 Schematic diagram of the SPS mold used in Examples 1, 2 and 3 of the present invention. DETAILED DESCRIPTION

[0036] The present invention will now be further described with reference to the embodiments and the accompanying drawings:

[0037] In order to improve the toughness of high entropy carbide ceramics, short-cut C fibers are selected for toughening, and they can be used for a long time in ultra-high temperature extreme environments. The present invention provides the following technical solutions:

[0038] A chopped fiber toughened high entropy carbide ceramic for use in ultra-high temperature extreme environments, characterized in that it comprises chopped fibers with a volume fraction of 5%-20% and a matrix of high entropy carbide.

[0039] Furthermore, the powders used for the matrix include TiC, NbC, TaC, VC, Mo, and C powders, the particle size range of TiC, NbC, TaC, VC, and Mo is 1-5 μm, and the particle size range of carbon powder is 10-50 nm.

[0040] Furthermore, the types of chopped fibers include SiC, C, and W, with a length of 1-10 mm, a diameter range of SiC and C fibers of 1-20 μm, and a diameter range of W fibers of 50-150 μm.

[0041] Furthermore, the molar ratio of the powders TiC, NbC, TaC, VC, Mo and C is 1:1:1:1:1:1.5-2.

[0042] At the same time, the present invention provides a method for preparing chopped fiber toughened high entropy carbide ceramics for use in ultra-high temperature extreme environments, which is special in that the above-mentioned chopped fibers and carbide powder are used, and the method comprises the following steps:

[0043] Step 1, powder preparation;

[0044] The six kinds of powders are mixed and then subjected to high-energy ball milling to mix the powders evenly and refine them.

[0045] Step 2, carbothermal reduction;

[0046] The powder was pre-pressed into a block at a pressure of 50 MPa, wrapped with a layer of graphite paper and placed in a graphite crucible. A carbon thermal reduction reaction was performed in a pressureless vacuum furnace to remove a small amount of oxygen in the commercial powder.

[0047] The heating rate is 5-10℃ / min, the temperature is raised to 1500-1800℃, and the temperature is kept for 2-3h.

[0048] The temperature is cooled to 500°C at a rate of 5-10°C / min, and then naturally cooled to room temperature along with the furnace to obtain a ceramic sample after carbon thermal reduction reaction and initial diffusion.

[0049] Step 3, grinding;

[0050] The carbothermally reduced ceramic samples were ground into powder for subsequent mixing with fibers.

[0051] Step 4: Chopped Fiber Deposition Interface and Mixing

[0052] The SiC or C fiber was cut to a length of 1-10 mm. The C chopped fiber was deposited with BN interface by CVI method, and the SiC chopped fiber was deposited with PyC interface by CVI method. The W fiber was deposited with Y2O3 by magnetron sputtering method and then cut to a length of 1-10 mm.

[0053] Step 5: Mixing fiber and matrix powder

[0054] The fibers at the deposited interface were mixed with the powder. The C and SiC chopped fibers were mixed by stirring, wet ball milling, and vacuum precipitation in sequence. The W chopped fibers were mixed manually.

[0055] Step 6: SPS sintering

[0056] The powder was placed in a graphite mold and sintered by the SPS method. After pre-pressing for 5 minutes at a minimum pressure of 0.8t, the temperature was raised to 1800℃ at 50-200℃ / min and the pressure was increased to 30-40MPa. The mixture was kept at 1800℃ and 30-40MPa for 10-20 minutes. After the insulation, the temperature was lowered to 600℃ at 50-200℃ / min and then naturally cooled in the furnace.

[0057] Furthermore, the step 1 specifically comprises: weighing the powder as a raw material, pouring it into an agate ball mill and adding WC grinding balls, the ball mill speed is 300r / min, and the ball milling is performed for 12-24h; after the ball milling is completed, the obtained powder is sieved using a sieve to obtain a matrix powder.

[0058] Furthermore, in step 3, the carbon thermal reduction requires that the ambient pressure is about 95 MPa lower than the external atmospheric pressure.

[0059] Furthermore, the specific steps of step 5 are as follows: pour anhydrous ethanol into a beaker and then slowly add SiC or C chopped fibers, stir at 400 r / min for 2 h using a vertical stirrer, then pour the powder into the ethanol and fiber mixture, evacuate and wet grind at 300 r / min for 12-24 h, after wet grinding, place the powder fiber mixture in a vacuum negative pressure environment for 2 h to allow the powder fiber mixture to precipitate, and then dry it in an oven at 70°C for 6-8 h

[0060] Furthermore, the mass ratio between WC grinding balls and powder during the ball milling process is 5-10:1.

[0061] Furthermore, the ratio of the mass of the SiC or C chopped fibers plus powder, the mass of ethanol, and the mass of grinding balls is 1:5:5-10.

[0062] In the embodiment, the short-cut fiber toughened high entropy carbide ceramic in ultra-high temperature extreme environment is characterized by: comprising short-cut fibers with a volume fraction of 5%-20%, and the matrix is ​​a high entropy carbide. The powder used for the matrix includes TiC, NbC, TaC, VC, Mo, and C powders. The particle size range of TiC, NbC, TaC, VC, and Mo is 1-5μm, and the particle size range of carbon powder is 10-50nm. The types of short-cut fibers include SiC, C, and W, with a length range of 1-10mm, the diameter of SiC and C fibers is 1-20μm, and the diameter of W fibers is 50-150μm.

[0063] Example 1

[0064] Step 1, preparing powder;

[0065] 0.0426 mol of carbide powder, 8.21 g of TaC powder, 2.55 g of TiC powder, 4.47 g of NbC powder, 2.68 g of VC powder, 4.08 g of Mo powder and 0.77 g of C powder were weighed as equimolar five-component carbide matrix raw materials; 0.0639 mol of C powder was used to allow carbon thermal reduction reaction to occur in a vacuum furnace to remove the inherent oxygen content in the commercial carbide powder.

[0066] Put the powder into the agate ball mill jar in turn, select 10mm, 5mm, and 1mm tungsten carbide grinding balls and mix them in from small to large quantities. The total mass of the grinding balls is 120g, and then put the agate ball mill jar into the stainless steel vacuum tank.

[0067] After vacuuming for 10 minutes, the mixture was ball-milled in a planetary ball mill at a speed of 300 r / min for 24 hours. After the ball milling was completed, the powder was taken out and passed through a 200-mesh sieve.

[0068] Step 2, carbothermal reduction;

[0069] The powder was pre-pressed into cylindrical blocks with a diameter of 25 mm on a tablet press, placed in a graphite crucible, and subjected to carbon thermal reduction reaction in a pressureless vacuum furnace. The process was started when the pressure in the furnace reached 95 MPa.

[0070] The heating rate is 5-10℃ / min, the temperature is raised to 1600℃, and kept at this temperature for 3h.

[0071] The temperature is cooled to 500°C at a rate of 5-10°C / min, and then naturally cooled to room temperature along with the furnace to obtain a ceramic sample after carbon thermal reduction reaction and initial diffusion.

[0072] Step 3, grinding;

[0073] The ceramic sample after carbon thermal reduction was ground into powder in an agate mortar with an agate pestle. At this time, the powder was a high entropy carbide powder with uneven element distribution after initial diffusion, and passed through a 200-mesh sieve.

[0074] Step 4, C fiber deposition interface;

[0075] The C fibers were cut into 2 mm length and placed in a graphite mold with holes, and a BN interface with a thickness of 800 nm was prepared in a deposition furnace by the CVI method.

[0076] Step 5, mixing the fiber and the matrix powder;

[0077] Take 22.5g of the ground powder, the calculated mass of the chopped C fiber at 5% volume fraction should be 0.298g, and mix with 110g of anhydrous ethanol, and stir at 400r / min for 2h using a vertical stirrer;

[0078] After stirring, the mixture was poured into an agate ball milling jar, 110 g of carbide grinding balls of different sizes were placed in it, vacuum was drawn, and the mixture was ball milled at 300 r / min for 24 h using a planetary ball mill;

[0079] After ball milling, pour the mixture into a clean beaker and precipitate it under the vacuum environment of a vacuum pump until the powder fibers reach the bottom of the cup and obvious stratification appears, which takes about 2 hours. After precipitation, put it in an oven and dry it at 70°C for 6 hours, and then grind the dried powder slightly to avoid caking.

[0080] Step 6, SPS sintering;

[0081] The powder is placed in the center of a circular cylindrical graphite mold, and a graphite gasket and a cylindrical graphite mold are placed above and below the powder respectively. The powder and the mold, and the molds are separated by graphite paper and placed in an SPS furnace.

[0082] Wait for the vacuum degree in the furnace to reach 1*10 -3 The post-operation process is to pre-press at the minimum pressure of 0.8t for 5 minutes, then increase the temperature to 2100℃ at 100℃ / min and the pressure to 30-40MPa, and keep it at 1800℃ and 30-40MPa for 10-20min; after the insulation, cool it to 600℃ at 100℃ / min, and then cool it naturally in the furnace.

[0083] Example 2

[0084] Step 1, preparing powder;

[0085] 0.0426 mol of carbide powder, 8.21 g of TaC powder, 2.55 g of TiC powder, 4.47 g of NbC powder, 2.68 g of VC powder, 4.08 g of Mo powder, and 0.77 g of C powder were weighed as equimolar five-element carbide matrix raw materials; 0.0639 mol of C powder was used to allow carbon thermal reduction reaction to occur in a vacuum furnace to remove the inherent oxygen content in the commercial carbide powder;

[0086] Put the powder into the agate ball mill in turn, select 10mm, 5mm, and 1mm tungsten carbide grinding balls from small to large quantities and mix them in, with a total mass of 120g of grinding balls, and then put the agate ball mill into a stainless steel vacuum tank;

[0087] After vacuuming for 10 minutes, the mixture was ball-milled in a planetary ball mill at a speed of 300 r / min for 24 hours. After the ball milling was completed, the powder was taken out and passed through a 200-mesh sieve.

[0088] Step 2, carbothermal reduction;

[0089] The powder was pre-pressed into cylindrical blocks with a diameter of 25 mm on a tablet press, placed in a graphite crucible, and subjected to carbon thermal reduction reaction in a pressureless vacuum furnace. The process was started when the pressure in the furnace reached 95 MPa.

[0090] The heating rate is 5-10℃ / min, the temperature is raised to 1600℃, and kept at this temperature for 3h.

[0091] The temperature was lowered to 500°C at a rate of 5-10°C / min, and then naturally cooled to room temperature along with the furnace to obtain a ceramic sample after carbon thermal reduction reaction and initial diffusion.

[0092] Step 3, grinding;

[0093] The ceramic sample after carbon thermal reduction was ground into powder in an agate mortar with an agate pestle. At this time, the powder was a high entropy carbide powder with uneven element distribution after initial diffusion, and passed through a 200-mesh sieve.

[0094] Step 4, SiC fiber deposition interface;

[0095] The SiC fiber was cut into 2 mm length and placed in a graphite mold with holes. A 400 nm thick PyC interface was prepared in a deposition furnace using the CVI method.

[0096] Step 5: Mixing fiber and matrix powder

[0097] Take 22.5g of the ground powder, the calculated mass of the chopped SiC fiber at 5% volume fraction should be 0.476g, and mix with 110g of anhydrous ethanol, and stir at 400r / min for 2h using a vertical stirrer;

[0098] After stirring, the mixture was poured into an agate ball milling jar, 110 g of carbide grinding balls of different sizes were placed in it, vacuum was drawn, and the mixture was ball milled at 300 r / min for 24 h using a planetary ball mill;

[0099] After ball milling, pour the mixture into a clean beaker and precipitate it under the vacuum environment of a vacuum pump until the powder fibers reach the bottom of the cup and obvious stratification appears, which takes about 2 hours. After precipitation, put it in an oven and dry it at 70°C for 6 hours, and then grind the dried powder slightly to avoid caking.

[0100] Step 6: SPS sintering

[0101] Place the powder in the center of the annular cylindrical graphite mold, put graphite gaskets and cylindrical graphite molds above and below the powder, and separate the powder and the mold, and the molds with graphite paper, and put them into the SPS furnace.

[0102] Wait for the vacuum degree in the furnace to reach 1*10 -3 The post-operation process is to pre-press at the minimum pressure of 0.8t for 5 minutes, then increase the temperature to 2100℃ at 100℃ / min and the pressure to 30-40MPa, and keep it at 1800℃ and 30-40MPa for 10-20min; after the insulation, cool it to 600℃ at 100℃ / min, and then cool it naturally in the furnace.

[0103] Example 3

[0104] Step 1, preparing powder;

[0105] 0.0426 mol of carbide powder, 8.21 g of TaC powder, 2.55 g of TiC powder, 4.47 g of NbC powder, 2.68 g of VC powder, 4.08 g of Mo powder and 0.77 g of C powder were weighed as equimolar five-component carbide matrix raw materials; 0.0639 mol of C powder was used to allow carbon thermal reduction reaction to occur in a vacuum furnace to remove the inherent oxygen content in the commercial carbide powder.

[0106] Put the powder into the agate ball mill jar in turn, select 10mm, 5mm, and 1mm tungsten carbide grinding balls and mix them in from small to large quantities. The total mass of the grinding balls is 120g, and then put the agate ball mill jar into the stainless steel vacuum tank.

[0107] After vacuuming for 10 minutes, the mixture was ball-milled in a planetary ball mill at a speed of 300 r / min for 24 hours. After the ball milling was completed, the powder was taken out and passed through a 200-mesh sieve.

[0108] Step 2, carbothermal reduction;

[0109] The powder was pre-pressed into cylindrical blocks with a diameter of 25 mm on a tablet press, placed in a graphite crucible, and subjected to carbon thermal reduction reaction in a pressureless vacuum furnace. The process was started when the pressure in the furnace reached 95 MPa.

[0110] The heating rate is 5-10℃ / min, the temperature is raised to 1600℃, and kept at this temperature for 3h.

[0111] The temperature was lowered to 500°C at a rate of 5-10°C / min, and then naturally cooled to room temperature along with the furnace to obtain a ceramic sample after carbon thermal reduction reaction and initial diffusion.

[0112] Step 3, grinding;

[0113] The ceramic sample after carbon thermal reduction was ground into powder in an agate mortar with an agate pestle. At this time, the powder was a high entropy carbide powder with uneven element distribution after initial diffusion, and passed through a 200-mesh sieve.

[0114] Step 4: W chopped fiber deposition interface

[0115] The W fiber was wound on a metal frame, and a 3 μm Y2O3 interface was deposited using reactive magnetron sputtering. The W fiber was then removed and cut to 2 mm.

[0116] Step 5: Mixing fiber and matrix powder

[0117] Take 22.5 g of the ground powder and calculate the mass of the chopped W fibers to be 2.873 g when the volume fraction is 5%, and shake by hand to mix.

[0118] Step 6: SPS sintering

[0119] Place the powder in the center of the annular cylindrical graphite mold, put graphite gaskets and cylindrical graphite molds above and below the powder, and separate the powder and the mold, and the molds with graphite paper, and put them into the SPS furnace.

[0120] Wait for the vacuum degree in the furnace to reach 1*10 -3 The post-operation process is to pre-press at the minimum pressure of 0.8t for 5 minutes, then increase the temperature to 2100℃ at 100℃ / min and the pressure to 30-40MPa, and keep it at 1800℃ and 30-40MPa for 10-20min; after the insulation, cool it to 600℃ at 100℃ / min, and then cool it naturally in the furnace.

[0121] Figure 1 This is the SEM image of the chopped C fiber toughened (TiTaNbVMo)C composite material after sintering, indicating that the fibers still maintain their original shape after sintering, the matrix elements are uniform except for a small amount of pores, and the fibers and matrix are well bonded.

[0122] Figure 2 This is the SEM image of the fracture morphology of the C / (TiTaNbVMo)C composite material sample after the fracture toughness test. Part of the fiber pullout and debonding appear in the image, and the pulled-out fibers and the holes left on the matrix after pulling out can be seen, indicating that the short-cut C fibers play a toughening role.

[0123] Figure 3The fracture toughness test results of pure ceramic (TiTaNbVMo)C and 5vol.% C, SiC, and W chopped fibers toughened respectively; compared with pure ceramic, the fracture toughness of C / (TiTaNbVMo)C is increased by 2.7723MPa·m -1 / 2 , increased by 38.64%; the fracture toughness of SiC / (TiTaNbVMo)C increased by 0.2509MPa·m -1 / 2 , increased by 3.49%; the fracture toughness of W / (TiTaNbVMo)C decreased.

[0124] The mechanical properties of the chopped fiber toughened (TiTaNbVMo)C prepared in the above examples 1, 2 and 3 were evaluated by fracture toughness. Figure 3 The results show that the fiber-reinforced ceramic composite material with excellent mechanical properties can be obtained by using the method of the present invention, wherein the toughening effect is best when the volume fraction of C chopped fiber is 5 vol.%, and the average fracture toughness is 9.9446 Mpa / m 1 / 2 .

Claims

1. A chopped fiber toughened high entropy carbide ceramic for use in ultra-high temperature extreme environments, characterized in that The invention comprises chopped fibers with a volume fraction of 5% to 20%, wherein the matrix is ​​high entropy carbide; the high entropy carbide is a mixture of TiC, NbC, TaC, VC, Mo and C powders; and the chopped fibers comprise SiC, C and W.

2. The chopped fiber toughened high entropy carbide ceramic for use in ultra-high temperature extreme environments according to claim 1, characterized in that: The molar ratio of TiC, NbC, TaC, VC, Mo and C is 1:1:1:1:1:1.5-2.

3. The chopped fiber toughened high entropy carbide ceramic for use in ultra-high temperature extreme environments according to claim 1, characterized in that: The particle size range of TiC, NbC, TaC, VC and Mo is 1-5 μm; the particle size range of carbon powder is 10-50 nm.

4. The chopped fiber toughened high entropy carbide ceramic for use in ultra-high temperature extreme environments according to claim 1, characterized in that: The length of the chopped fibers is 1-10 mm, the diameters of SiC and C fibers are in the range of 1-20 μm, and the diameter of W fibers is in the range of 50-150 μm.

5. A method for preparing the chopped fiber toughened high entropy carbide ceramic for use in ultra-high temperature extreme environments as claimed in any one of claims 1 to 4, characterized in that Here are the steps: Step 1: Mix TiC, NbC, TaC, VC, Mo and C powders and perform high-energy ball milling to obtain mixed powder; Step 2, carbothermal reduction: pre-press the powder into blocks and perform carbothermal reduction reaction in a vacuum furnace without pressure to remove a small amount of oxygen in the commercial powder to obtain a preform; The carbon thermal reduction process is: heating up to 1500-1800°C at a rate of 5-10°C / min, keeping the temperature for 2-3h; cooling down to 500°C at a rate of 5-10°C / min, and then naturally cooling to room temperature with the furnace to obtain a ceramic product after carbon thermal reduction reaction and preliminary diffusion; Step 3: Grind the carbon thermally reduced ceramic product into powder; Step 4, fiber deposition interface and mixing: SiC or C fiber is cut to 1-10 mm, and BN interface is deposited by CVI method for short fiber C; PyC interface is deposited by CVI method for short SiC fiber; Y2O3 is deposited by magnetron sputtering method for W fiber, and then cut to 1-10 mm length as short fiber; Step 5, mixing fibers and matrix powder: mixing the fibers with the powder after the interface deposition, mixing the C and SiC chopped fibers by stirring, wet ball milling, and vacuum precipitation in turn; mixing the W chopped fibers in a natural state; and then mixing the two to obtain a mixed powder; Step 6, SPS sintering: the mixed powder is placed in a graphite mold and sintered by the SPS method to obtain chopped fiber-reinforced high-entropy carbide ceramics for use in ultra-high temperature extreme environments; The SPS sintering process parameters are: heating to 1800-2100°C at 50-200°C / min, increasing the pressure to 30-40MPa, keeping at 1800-2100°C and 30-40MPa for 10-20min; cooling at 50-200°C / min after the insulation, and cooling naturally in the furnace; Chopped fiber-reinforced high-entropy carbide ceramics for use in ultra-high temperature extreme environments are obtained.

6. The method according to claim 5, characterized in that: In the step 1, the powder is poured into an agate ball mill and tungsten carbide grinding balls are added, the ball mill speed is 300-400 r / min, and the ball milling is performed for 12-24 hours; after the ball milling is completed, the obtained powder is sieved using a sieve to obtain a matrix powder.

7. The method according to claim 6, characterized in that: The mass ratio of the tungsten carbide grinding balls to the powder is 5-10:1; during the wet grinding, the mass ratio of the SiC, C chopped fibers plus the powder, the ethanol, and the grinding balls is 1:5:5-10.

8. The method according to claim 5, characterized in that: In the step 3: during carbon thermal reduction, the ambient pressure is required to be 95-98 MPa lower than the external atmospheric pressure.

9. The method according to claim 5, characterized in that: In the step 5: pour anhydrous ethanol into a beaker and then slowly put in the fiber, use a vertical stirrer to stir at 400 r / min for 2 hours, then pour the powder into the ethanol and fiber mixture, evacuate and wet grind at 300 r / min for 12-24 hours, after wet grinding, place in a vacuum negative pressure environment for 2 hours to allow the powder fiber mixture to precipitate, and then dry in an oven at 70°C for 6-8 hours.

10. A chopped fiber toughened high entropy carbide for use in ultra-high temperature extreme environments as claimed in any one of claims 1 to 4 The application of ceramics is characterized by: The short fiber toughened high entropy carbide ceramics reach 9.9446MPa.m -1 / 2 , Excellent mechanical properties, used in ultra-high temperature extreme environments.

Citation Information

Patent Citations

  • Shaped bodies containing short inorganic fibers

    CA2047739A1

  • Novel fiber-toughened ceramic-based composite material and preparation method and application thereof

    CN113233909A

  • High-entropy ultrahigh-temperature ceramic-based composite material and preparation method thereof

    CN115385712A

  • High-strength, high-toughness and high-entropy carbonitride ceramic and preparation method thereof

    CN115448740A

  • Method for refining transition high-entropy carbide ceramic grains

    CN116947496A

Cited By

  • A non-metal / metal co-doped high-entropy carbide ceramic composite material and a preparation method thereof

    CN122771773A